Safety and efficacy of tazarotene foam for the treatment of acne vulgaris - Epstein E; Stein Gold L (Dove Medical Press, 2013)
Erica L Epstein, Linda Stein GoldHenry Ford Hospital, Detroit, MI, USABackground: Tazarotene foam is the first topical retinoid foam approved for the treatment of acne vulgaris.Objective: To review the safety and efficacy studies of tazarotene foam in the treatment of moderate to severe acne.Methods: Five Phase I safety studies in normal controls are reviewed and two Phase III safety and efficacy studies in patients with moderate to severe acne are reviewed.Conclusion: Tazarotene foam, 0.1% was effective in the treatment of moderate to severe acne vulgaris with an acceptable tolerability profile. This treatment provides a cosmetically favorable alternative for topical retinoid therapy.Keywords: tazarotene, acne, foam, topical retinoid